Evaluasi Penerapan Kerjasama Pemerintah - Swasta Dalam Pembangunan dan Pengelolaan Pasar Desa Penyangkringan - Weleri - Kabupaten Kendal (Tinjauan Aspek Finansial dan Aspek Ekonomi) - Rahutama, Ryan (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
Penyangkringan villages became one village into the Center for Environmental Activities (PKL) to the service center functions as a center of trade and services in accordance with the Spatial Kendal Year 2011-2031. The village where Penyangkringan have potential cash asset village that has not been optimally and can not accommodate these activities so that the village government plans to build a village market. But with a limited budget, cooperation with the private sector to be the solution to overcome it. Authorities village rural market development cooperation with built-operate-transfer (BGS) with a contract term of 10 years. Therefore we need a study evaluating the implementation of the cooperation that focus on the financial feasibility and economic aspects. The purpose of this study was to evaluate the implementation of village government and private partnership in the development of rural markets in financial aspects and economic aspects. Financial and economic aspects views of four criteria: Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Pay Back Period (PBP). The results showed that the financial results obtained Rp. 193.610.176 (NPV), 13,5 % (IRR), 1,035 (BCR), and 4 Years, 3 Months (PBP), while economically the results obtained Rp. 143.437.317 (NPV), 11,6 % (IRR), 1,01 (BCR) and 4 Years, 4 Months (PBP)